Sociodynamics of Students’ Digital Capital in the Context of the COVID-19 Epidemiological Crisis: an Experience of a Mixed Strategy of Empirical Research - P. P. Deryugin; O. S. Bannova; E. A. Kamyshina; V. E. Yarmak; K. E. Salfetnik (Дискурс)
Introduction. The sociodynamics of students’ digital capital in the context of an epidemiological crisis has acquired special characteristics. The speed, focus and technologies for the formation of digital capital have changed significantly and are expressed in new content features and characteristi cs of sociodynamics.Methodology and sources. An integrative approach to the study and analysis of the digital capital sociodynamics is used, which consists a set of theoretical and methodological positions in the study of digital capital proposed by resea rchers earlier. An approach to the sociological interpretation of the concept of digital capital, which is characterized by systemic and integrative characteristics, is presented. The formed theoretical and methodological platform served as the basis for c onstructing an empirical research methodology.Results and discussion. Methodological approaches to the digital capital definition as an object of research are generalized. The contradictions and fragmentation in the interpretation of digital capital in private research and the relevance of sociological understanding of the essence of digital capital are shown. The tendencies and trends of the sociodynamics of digital capital during the pandemic have been empirically confirmed.Conclusion. The article presents some trends in the sociodynamics of students’ digital capital in a pandemic: first, the stimulating role of the pandemic in the development of digital competencies; secondly, changes in the direction of mastering digital competencies; third, analysis of the activity and intensity of changes in digital competencies; fourth, the intensification of the development of digital technologies related to the social aspects of interaction in the context of a lockdown.